2014
DOI: 10.2174/1389450115666140826122315
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance in High-Grade Gliomas: Relevance of Adenosine Signalling in Stem-Like Cells of Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is the most common glial cell-derived brain tumour, with one of the worst prognoses among all cancers. GBM cells are infiltrative and extremely resistant to radio- and chemotherapy, which inevitably leads to recurrence after surgical resection. These inherent GBM properties are the reasons that patient treatment has not seen major improvements in decades. Studies have consistently shown that glioblastoma stem-like cells (GSCs) are responsible for the tumourigenic properties in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…While it is known that hypoxia promotes chemoresistance, the mechanisms are not yet fully understood. It has been shown that nucleoside adenosine, which is elevated in the tumour microenvironment, plays a prominent role in mediating resistance mechanisms [ 148 ]. Therefore, hypoxic conditions may be a functional component of the stem cell niche, which highlights the close relationship between the maintenance of stem cell phenotype and chemoresistance.…”
Section: Abc Transporters and Tumour Metabolismmentioning
confidence: 99%
“…While it is known that hypoxia promotes chemoresistance, the mechanisms are not yet fully understood. It has been shown that nucleoside adenosine, which is elevated in the tumour microenvironment, plays a prominent role in mediating resistance mechanisms [ 148 ]. Therefore, hypoxic conditions may be a functional component of the stem cell niche, which highlights the close relationship between the maintenance of stem cell phenotype and chemoresistance.…”
Section: Abc Transporters and Tumour Metabolismmentioning
confidence: 99%
“…Although cancers, such as GBM, may be intrinsically resistant to therapy, the ability to engage survival mechanisms in response to treatment potentially further reduces efficacy of any promising agent [3][4][5] Autophagy is one such conserved cellular pathway. The process removes dysfunctional or damaged organelles through lysosomal degradation and recycles the products for cellular metabolic needs [6].…”
Section: Introductionmentioning
confidence: 99%
“…This resistance also leads to the recurrence of glioblastoma following standard cancer therapy. Accumulating evidence suggests that glioblastoma stem cells are the major cause of chemo- and radio-resistance and are largely responsible for tumor recurrence ( 46 49 ). Therefore, the glioblastoma stem cell population is an important target for the successful clinical management of progressive and recurrent malignant glioblastoma.…”
Section: Brm270 Overcomes Chemoresistance By Targeting Cancer Stem Cementioning
confidence: 99%